A 12‐week, randomized, parallel‐group, proof‐of‐concept study of tulobuterol patch and salmeterol inhaler as add‐on therapy in adult‐onset mild‐to‐moderate asthma. (January 2017) - Inoue, Hideki; Niimi, Akio; Matsumoto, Hisako; Ito, Isao; Oguma, Tsuyoshi; Otsuka, Kojiro; Takeda, Tomoshi; Nakaji, Hitoshi; Tajiri, Tomoko; Iwata, Toshiyuki; Nagasaki, Tadao; Mishima, Michiaki
Summary: Patch formulation of tulobuterol has been used in asthma treatment as a long‐acting β2 ‐agonist (LABA) through sustained skin absorption. Its treatment efficacy, especially in small airways, remains poorly understood. The study aim was to investigate LABA add‐on effects of tulobuterol patch (TP) and salmeterol inhaler (SA) on pulmonary function, asthma control and health status. Patients who had adult‐onset under‐control asthma, despite taking inhaled corticosteroids, were enrolled in a randomized, open‐label, parallel‐group, proof‐of‐concept study of 12‐week add‐on treatment with TP (n=16) or SA (n=17). Spirometry, impulse oscillometry (IOS), exhaled nitric oxide levels, and clinical questionnaires of asthma control, health status (St. George's Respiratory Questionnaire: SGRQ), and symptoms were evaluated every 4 weeks. Add‐on treatment of SA significantly improved the spirometric indices of small airway obstruction (forced expiratory flow between 25% and 75% of FVC: FEF25‐75, and maximum expiratory flow at 25% of FVC: MEF25 ) and IOS indices of whole respiratory resistance (resistance at 5 Hz) as compared to TP. In intra‐group comparisons, add‐on treatment of TP improved the scores of the asthma control test and the total SGRQ, as well as the symptom and impact components of the SGRQ. SA add‐on treatment improved FEV1 and IOS parameters of resistance at 20 Hz and reactance at 5 Hz. Neither of the treatments improved exhaled nitric oxide levels. In conclusion, add‐on treatment of TP improved asthma control and health status, whereas SA improved pulmonary function measures associated with large and small airway involvement among patients with adult‐onset mild‐to‐moderate asthma.